(3+x)/(x-3)-3<0
[(3+x)-3(x-3)]/(x-3)<0
(3+x-3x+9)/(x-3)
(12-2x)/(x-3)<0
12-2x<0 ^ x-3>0 v 12-2x>0 ^ x-3<0
↓↓↓↓↓↓
x>6 ^ x>3 v x<6 ^ x<3
]6;∞[ U ]-∞;3[
↓
]-∞;3[ U ]6;∞[
10-4(2x+5)=6y-13
4y-63=5(4x-2y)+2
4y-63-20x+10y-2=0
14y-65-20x=0
x=0.7y-3.25
3-8x-6y=0
3-8*(0.7y-3.25)-6y=0
3-5.6y+26-6y=0
29-11.6y=0
y=29/11.6y=2.пятых
14*2.5-65-20x=0
-30-20x=0
x=-30/20
x=-1.5
(3+x)/(x-3)-3<0
[(3+x)-3(x-3)]/(x-3)<0
(3+x-3x+9)/(x-3)
(12-2x)/(x-3)<0
12-2x<0 ^ x-3>0 v 12-2x>0 ^ x-3<0
↓↓↓↓↓↓
x>6 ^ x>3 v x<6 ^ x<3
]6;∞[ U ]-∞;3[
↓
]-∞;3[ U ]6;∞[